What to expect after revision shoulder arthroplasty? A comprehensive review of the literature - Merolla, Giovanni; D'Ambrosi, Riccardo; Buda, Matteo; Sircana, Giuseppe; Bellato, Enrico; Fogliata, Valentina; De Cupis, Mauro; Tarallo, Luigi; Micheloni, Gian Mario; Sperling, John W (Acta Biomedica Atenei Parmensis, 2023)
The number of shoulder arthroplasties has increased tremendously over the last twenty years, creating a proportional increase in complications rates and revision. Shoulder arthroplasty surgeon should have a clear understanding of the reasons for failure based on the specific index procedure that was performed. The main challenge includes the need for component removal and managing glenoid and humeral bone defects. This manuscript aims to outline the most common indications for revision surgery and treatment options based on a careful and detailed review of the available literature.  This paper should help the surgeon in patient evaluation and selection of the optimal procedure for an individual patient.